The role of microglia in Neuroinflammation associated with cardiopulmonary bypass - Meng, Lingda; Gu, Tianxiang; Yu, Peng; Zhang, Zhiwei; Wei, Zhijing (Frontiers in Cellular Neuroscience, 2024)
Cardiopulmonary bypass (CPB) and deep hypothermic circulatory arrest (DHCA) are indispensable core techniques in cardiac surgery. Numerous studies have shown that cardiopulmonary bypass and deep hypothermic circulatory arrest are associated with the occurrence of neuroinflammation, accompanied by the activation of microglia. Microglia, as macrophages in the central nervous system, play an irreplaceable role in neuroinflammation. Current research on neuroinflammation induced by microglia activation mainly focuses on neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, neuropathic pain, acquired brain injury, and others. However, there is relatively limited research on microglia and neuroinflammation under conditions of cardiopulmonary bypass and deep hypothermic circulatory arrest. The close relationship between cardiopulmonary bypass, deep hypothermic circulatory arrest, and cardiac surgery underscores the importance of identifying targets for intervening in neuroinflammation through microglia. This could greatly benefit cardiac surgery patients during cardiopulmonary bypass and the perioperative period, significantly improving patient prognosis. This review article provides the first comprehensive discussion on the signaling pathways associated with neuroinflammation triggered by microglia activation, the impact of cardiopulmonary bypass on microglia, as well as the current status and advancements in cardiopulmonary bypass animal models. It provides new insights and methods for the treatment of neuroinflammation related to cardiopulmonary bypass and deep hypothermic circulatory arrest, holding significant importance for clinical treatment by cardiac surgeons, management strategies by cardiopulmonary bypass physicians, and the development of neurologically related medications.